2013
DOI: 10.1080/10942912.2012.654559
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Antioxidant Constituents and Anti-Oxidative Properties of Vegetable Soybean

Abstract: Vegetable soybean is fast becoming a popular nutritious snack outside SouthEastern countries where its consumption is in vogue since ages. Reports have appeared in the literature concerning the nutritional value of green seeds; however, the information on its antioxidative properties is lacking. In the present investigation, 16 vegetable-type soybeans were evaluated for antioxidant constituents and antioxidative properties at picking stage. Vitamin C, total phenolic content, and total isoflavone were significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Total phenol content in green seeds ranged from 0.68 to 1.39 mg gallic acid equivalent g -1 . Antiradical activity varied from 10 to 25% (Kumar et al, 2014). In another investigation in India, ten different vegetable soybean genotypes were compared.…”
Section: Yield Qualitymentioning
confidence: 99%
“…Total phenol content in green seeds ranged from 0.68 to 1.39 mg gallic acid equivalent g -1 . Antiradical activity varied from 10 to 25% (Kumar et al, 2014). In another investigation in India, ten different vegetable soybean genotypes were compared.…”
Section: Yield Qualitymentioning
confidence: 99%
“…It was concluded that compared to the first day, at the end of the study, the vitamin C content decreased in all samples, seeing that it dropped to 54% (C), 73% (B) and 73% for BO sample. Kumar with colleagues reported that significant genotypic variations in vitamin C content have been identified by analyzing 16 vegetable soybean green pods 34.8-88.7 mg 100 g -1 (Kumar et al, 2014). Czaikoski et al (2012) identified a 19.6% reduction in vitamin C after four days of storage of blanched soybeans at 5 °C.…”
Section: Soluble Solids Content (Ssc)mentioning
confidence: 99%
“…Molecular ozone reactions are selective and limited to unsaturated aromatic and aliphatic compounds, as the ozone reaction with ascorbate is faster than with double bond compounds (fatty acids) (Kumar et al, 2014;Glowacz et al, 2015).…”
Section: Soluble Solids Content (Ssc)mentioning
confidence: 99%